Plot size related to numbers of treatments, repetitions, and the experimental precision in flax - Cargnelutti Filho, Alberto; Neu, Ismael Mario Márcio; Santos, Gustavo Oliveira dos; Facco, Giovani; Wartha, Cleiton Antonio; Kleinpaul, Jéssica Andiara (Comunicata Scientiae, 2019)
The aim of this study was determining the optimum plot size to evaluate the fresh matter of aerial part in flax (Linum usitatissimum L.), in scenarios formed by combinations of numbers of treatments, number of repetitions, and precision levels. The fresh matter of aerial part was weighed on 144 basic experimental units of 1.00 m × 1.00 m in uniformity trial with size of 12 m × 12 m (144 m2). It was estimated the soil heterogeneity index of Smith (1938). Also, the optimum plot size was determined by the Hatheway’s method (1961) in scenarios formed by combinations of i treatments (i = 5, 10, 15, and 20), r repetitions (r = 3, 4, 5, 6, 7 8, 9, and 10), and d precision levels (d = 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, and 40%). In experiments planned on randomized block design, with 5 to 20 treatments and four repetitions, plots with 7 m2 are sufficient to identify significant differences between treatments regarding fresh matter of aerial part in flax, at 5% probability, of 34% of the experiment overall mean.